Understanding the Psychological Perspective of Political Trust in Indonesia Context - Indro Adinugroho (Buletin Psikologi, 2021)
Political trust, conceptually understood as a trust in politics, refers to the positive expectation from the citizen that the government, as an institution leader, will deliver citizen’s best interest through policies and regulations. Political trust is considered as one of the indicators that mark legitimation of existing government in addition to the result from election. Trust in politics is a fundamental element that can connect government and citizens for which benefit policies acceptance and avoid political conflict. The dynamic interaction between government and citizens is the most valuable aspect in democracy, of which the government, as the highest administrator, carries aspiration from the public. For Indonesia, a democratic country with its uniqueness in culture, it is crucial to investigate factors that might contribute as the dimensions of political trust. Such comprehensive understanding can inform the betterment of the democratic practices in Indonesia towards a more robust democracy. In this review study, the author analyzed political trust from a psychological perspective and proposes four basic dimensions to understand political trust from Indonesian perspective. These are cultural dimension, gender dimension, subjective preference dimension, and performance dimension.